The Human Skin Microbiome in Selected Cutaneous Diseases - Carmona-Cruz, Silvia; Orozco-Covarrubias, Luz; Sáez-de-Ocariz, Marimar (Frontiers in Cellular and Infection Microbiology, 2022)
The human skin harbors a wide variety of microbes that, together with their genetic information and host interactions, form the human skin microbiome. The role of the human microbiome in the development of various diseases has lately gained interest. According to several studies, changes in the cutaneous microbiota are involved in the pathophysiology of several dermatoses. A better delineation of the human microbiome and its interactions with the innate and adaptive immune systems could lead to a better understanding of these diseases, as well as the opportunity to achieve new therapeutic modalities. The present review centers on the most recent knowledge on skin microbiome and its participation in the pathogenesis of several skin disorders: atopic and seborrheic dermatitis, alopecia areata, psoriasis and acne.